Dorotea & Miguel - Kasza, Keiko (Bogotá : Grupo Editorial Norma, 2001)
Three short stories featuring best friends Dorothy and Mikey that emphasize caring and sharing despite their individual differences.
K-3
Text in Spanish.
Translation of: Dorothy & Mikey.
K-3
Keywords: Friendship -- Fiction; Spanish language materials; Play -- Fiction; Competition (Psychology) -- Fiction; Friendship -- Fiction; Spanish language; Play -- Fiction; Competition -- Fiction